2018
DOI: 10.1590/1980-549720180019.supl.1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneidade de comportamentos de risco à saúde bucal em adolescentes: evidência da Pesquisa Nacional de Saúde do Escolar

Abstract: Objective: To investigate the prevalence of simultaneous oral health risk behaviors and associated factors among Brazilian adolescents. Methods: The study comprised data of 109,104 adolescents participating in the Brazilian National School-based Student Health Survey. The simultaneous presence of less frequent toothbrushing (E), current smoking (C), no visits to the dentist (D), low fruit intake (F), and high sugar intake (A) was assessed by comparison of observed/expected prevalence (OP/EP). Logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(42 reference statements)
0
4
0
4
Order By: Relevance
“…Assim, Jordão et al (2018), reforçam que estratégias educativas voltadas para pais de pré-escolares são altamente valiosas, uma vez que seu comportamento em relação à saúde bucal tem influência direta no número de cáries dentárias de seus filhos. As atitudes dos pais têm um impacto positivo no estado da saúde bucal das crianças; como os pais controlam a escovação dentária e o consumo de açúcar, as crianças desenvolvem hábitos positivos de saúde bucal.…”
Section: Resultsunclassified
“…Assim, Jordão et al (2018), reforçam que estratégias educativas voltadas para pais de pré-escolares são altamente valiosas, uma vez que seu comportamento em relação à saúde bucal tem influência direta no número de cáries dentárias de seus filhos. As atitudes dos pais têm um impacto positivo no estado da saúde bucal das crianças; como os pais controlam a escovação dentária e o consumo de açúcar, as crianças desenvolvem hábitos positivos de saúde bucal.…”
Section: Resultsunclassified
“…Nevertheless, this relation might not be causal, and this phenomenon is still not elucidated. A recent study based on the PenSE database [18] indicated that in fact the prevalence of simultaneous oral health-risk behaviors is associated with sociodemographic factors-family supervision is highlighted as a protective factor for multiple oral health-risk behaviors, which adds evidence to the importance of family's role in an adolescents' health-related choices. Although the mechanistic explanation for this association is still under debate, it reinforces that oral health self-assessment might play a role as a proxy variable for other health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A fim de superar as desigualdades sociais e estabelecer uma saúde bucal de maneira igualitária para a população, a política utilizou os princípios do Sistema Único de Saúde (SUS), constituindo-se como uma área de integralidade, que articula além dos três níveis de atenção, as ações multidisciplinares, multiprofissionais e intersetoriais (Brasil, 2018). Em áreas de baixo nível socioeconômico, para alcançar o sucesso nas medidas públicas de saúde bucal é primordial que a equipe interdisciplinar alcance as mães e as informem sobre os benefícios gerados em manter uma rotina de higiene bucal nela e nos seus filhos (Blomma & Krevers, 2020;Jordão, Malta & Freire, 2018).…”
Section: Introductionunclassified